2007
DOI: 10.1177/030857590703100305
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Information on How the Attachment Difficulties of Adopted and Looked after Children Affect their Schooling

Abstract: The loss, separation and trauma experienced by looked after and adopted children can seriously affect their school life and ability to learn. A great deal has been written and researched on the low educational achievement of looked after children, but there is much less available on how adopted children fare. An attachment perspective can make a valuable contribution to understanding the learning needs of vulnerable children. Rena Phillips discusses a successful initiative by PACS, a small post-adoption suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Many of these emotions echo feelings reported in other studies of looked after children moving school; they too described feeling scared and lonely, sometimes causing anxiety and depression, magnifying and exacerbating any feelings of insecurity and uncertainty which they already have (Children’s Commissioner for England, 2019). While recognising that not all moves for looked after children lead to poor outcomes, the impact of multiple changes is amplified for many by virtue of their previous experiences, and these can impact negatively on their schooling and affect their relationships with peers and staff (Pecora, 2012; Phillips, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these emotions echo feelings reported in other studies of looked after children moving school; they too described feeling scared and lonely, sometimes causing anxiety and depression, magnifying and exacerbating any feelings of insecurity and uncertainty which they already have (Children’s Commissioner for England, 2019). While recognising that not all moves for looked after children lead to poor outcomes, the impact of multiple changes is amplified for many by virtue of their previous experiences, and these can impact negatively on their schooling and affect their relationships with peers and staff (Pecora, 2012; Phillips, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Attachment disorder is now acknowledged in the Department for Education's advice on mental health and behaviour in school (DfE 2015). However, interest in human attachments and their significance in the school environment is broader that the topic of health (see for example, Clements 2013;Geddes 2006;Marshall 2014;Phillips 2007;Ubha and Cahill 2014;and Webber 2017). As with social work, as indicated above, the practice literature relating to education is often eclectic in approach.…”
Section: Promoting Family Membershipmentioning
confidence: 99%
“…A further study of 102 looked-after children found that 32 of them reported actual or potential self-harm, and that across all the participants, lower academic self-esteem was an issue, being more prevalent among the group that reported self-harm [15]. The long-term impact of early disadvantage, abuse and neglect upon attention and memory functioning was the focus of a paper by Phillips [16]. She argues that this effect can occur in two different ways.…”
Section: Literature Reviewmentioning
confidence: 99%